The Effect of Marketing on Student Loyalty in Indomie, Sedap, and ABC Instant Noodle Products with Moderated Variations - Diani Arthantri (Institute of Computer Science (IOCS), 2022)
This research was conducted at a typical souvenir shop from Riau